Design of petroleum company's metadata and an effective knowledge mapping methodology - Nimmagadda, Shastri; Dreher, Heinz (IASTED - International Association of Science and Technology for Development, 2007)
Success of information flow depends on intelligent datastorage and its management in a multi-disciplinaryenvironment. Multi-dimensional data entities, data typesand ambiguous semantics, often pose uncertainty andinconsistency in data retrieval from volumes of petroleumdata sources. In our approach, conceptual schemas andsub-schemas have been described based on variousoperational functions of the petroleum industry. Theseschemas are integrated, to ensure their consistency andvalidity, so that the information retrieved from anintegrated metadata (in the form of a data warehouse)structure derives its authenticity from its implementation.The data integration process validating the petroleummetadata has been demonstrated for one of the Gulfoffshore basins for an effective knowledge mapping andinterpreting it successfully for the derivation of usefulgeological knowledge. Warehoused data are used formining data patterns, trends and correlations amongknowledge-base data attributes that led to interpretation ofinteresting geological features. These technologies appearto be more amenable for exploration of more petroleumresources in the mature gulf basins.